UNFAIR INFORMATION PRACTICES RELATED TO MEAT AND MEAT PRODUCTS IN POLAND - Kowalska, Aleksandra (Proceedings of the International Scientific Conference "Economic Sciences for Agribusiness and Rural Economy", 2018)
The aim of this paper was to recognize the scale and types of the food adulteration practices associated with meat and meat products from Poland. The vulnerability of food supply chains to fraud/adulteration is growing as a result of globalisation, which is expanding the scope and scale of the incidence of food fraud/adulteration. Both the intentional and unintentional adulteration of food can lead to a public health threat, and cause severe economic consequences. Meat and meat products are the most common targets for adulteration in Poland and the EU. Since meat and meat products hold a key position in food production and consumption in Poland, it is in both the industry’s and government’s interests to eliminate adulteration in the meat supply chain. The methodological approach was to first review the literature to define and outline the challenge of food adulteration, and then to build a database on the basis of IJHARS decisions regarding adulterated meat and meat products, and to analyse them in detail. An analysis of the data revealed that most cases infringed Article 7.1(a) of Regulation (EU) 1169/2011 on the provision of food information to consumers concerning fair information practices.